Prostorova model tsinotvorennya u budivnitvі - Sorokinа, L.; Gojko, А.; Kovalenko, Y. (Ways to Improve Construction Efficiency, 2018)
The influence of the spatial factor on the average cost of housing construction and the dynamics of its change in time is investigated in the article. Power dependences of the cost of building a square meter of housing in the region have been constructed to approximate the regularity "rank-size" in 2015 - 2017. The obtained results can be used by the managers of budget funds, developers and investors to justify the feasibility and feasibility of housing projects, designers and contractors for the preparation of technical and economic calculations and proposals for the preparation of contractual prices for the performance of work.